STRATEGI PENINGKATAN USAHA RUMAH TANGGA PERIKANAN HAND LINE DI NEGERI HUKURILA KECAMATAN LEITIMUR SELATAN - Mahrum Rumkel; Hellen Nanlohy; Saiful Saiful (Universitas Pattimura, 2022)
The potential resources on the coast and oceans must be managed wisely and wisely. Fishery households (RTP) are one of the fishery units that can manage fishery resources. The purpose of this study is to find out the internal and external factors of the RTP and formulate a strategy to increase the business of the RTP hand line in Hukurila Village. The method used in this study was descriptive with a sample of 10 RTP. The analysis uses descriptive analysis and SWOT. Identification of internal factors, namely the availability of fishery resources and increased catches but low human resources, no cold storage available and limited capital. External factors are access to resources, government assistance, market availability, availability of fishing grounds. The threats are the arrest season, lack of capital information, high fuel oil prices and the presence of social conflicts. The SWOT analysis formulates an increase in fishermen's capacity in the development of an increased fleet, optimization of marketing of capture production, and increasing fishermen's access to reach fishing grounds.